Pencegahan stunting di Puskesmas Rawat Inap Kemiling Kota Bandar Lampung - Wardiyah, Aryanti; Adha, Adinda Wulan; Palupi, Antika; Budiarti, Budiarti; Wulandari, Hesti; Pratiwi, Liza Ayu; Nepiana, Nurul; Saputra, Raihan; Hidayat, Taufiq; Kurniawan, Yogi (Indonesian Public Health-Observer Information Forum (IPHORR) Kerja sama dengan: Unit Penelitian dan Pengabdian Kep Akademi Keperawatan Baitul Hikmah, 2024)
Background: Stunting is a condition where there is a lack of nutrition which causes the baby to be born earlier than it should be, it can be due to weight, maternal nutrition and fetal growth and development. Purpose: To improve knowledge about stunting prevention at the Kemiling Inpatient Health Center, Bandar Lampung City. Method: The implementation of this activity goes through several stages, namely asking permission from the head of the MBTS room to explain about stunting to the child's parents, providing media that will be used for counseling in the form of leaflets, purchasing tools and materials for implementing counseling activities. Results: The initial step before the activity was carried out by the survey team who conducted observations and interviews with the health center, the results of which were obtained from observations and interviews regarding stunting prevention, namely the lack of parental knowledge about stunting. In accordance with the results of the observation, it was obtained that the provision of health counseling about stunting prevention was still poorly known by parents. The implementation was carried out on January 2, 2024 at the Kemiling Health Center, Bandar Lampung City, when the implementation, parents were given education and presentation of childbirth preparation material. Conclusion: Stunting is a condition of chronic malnutrition due to inadequate nutritional intake and not in accordance with nutritional needs. The main factors causing stunting are: Food intake for survival. Low sanitation and environmental cleanliness can cause infectious diseases that disrupt the digestive tract. The impact of stunting is disruption of social life, disruption of the economy in the community, disruption of health, education and productivity of children in the future. In addition, stunting also results in disruption of gross and fine motor development. Keywords: Prevention; Society; Stunting. Pendahuluan: Stunting adalah kondisi dimana gizi kurang sehingga mengakibatkan bayi lahir lebih awal dari seharusnya, bisa dikarenakan berat badan, gizi ibu dan tumbuh kembang janin. Tujuan: Untuk meningkatkan pengetahuan tentang pencegahan stunting di Puskesmas Rawat Inap Kemiling Kota Bandar Lampung. Metode: Pelaksanaan kegiatan ini melalui beberapa tahapan yaitu meminta izin kepada kepala ruang mbts untuk menjelaskan tentang stunting kepada orangtua anak, menyediakan media yang akan digunakan untuk penyuluhan berupa media leaflet, membeli alat dan bahan untuk pelaksanaan kegiatan penyuluhan. Hasil: Langkah awal sebelum kegiatan dilakukan oleh tim survey yang melakukan observasi dan wawancara dengan pihak puskesmas yang hasilnya diperoleh dari observasi dan wawancara seputar pencegahan stunting yaitu kurangnya pengetahuan orangtua tentang stunting. Sesuai dengan hasil observasi diperoleh bahwa pemberian penyuluhan kesehatan tentang pencegahan stunting masih kurang diketahui oleh orangtua. Implementasi telah dilaksanakan pada tanggal 02 Januari 2024 di Puskesmas Kemiling Kota Bandar Lampung, ketika implementasi orangtua diberikan edukasi serta pemaparan materi persiapan persalinan. Simpulan: Stunting merupakan kondisi kurang gizi kronis karena asupan gizi yang kurang dan tidak sesuai kebutuhan gizi. Faktor utama penyebab stunting adalah: Asupan makanan untuk kelangsungan hidupnya. Rendahnya sanitasi dan kebersihan lingkungan dapat menyebabkan penyakit infeksi yang mengganggu saluran pencernaan. Dampak Stunting yaitu terganggunya kehidupan sosial, terganggunya ekonomi di masyarakat, mengganggu kesehatan, Pendidikan dan produktifitas anak dikemudian hari. Selain itu stunting juga mengakibatkan terganggunya perkembangan motorik kasar maupun halus.